Differences in some morphological characteristics and repetitive strength in relation to age in handball players - Slavka Durlević; Milica Mijajlović; Marija Durlević (University of Novi Sad, Faculty of Sport and Physical Education, 2023)
Many different anthropological parameters contribute to achieving top success in handball. Morphological characteristics and repetitive strength have been shown through scientific and practical work to be one of the most important indicators of success. Therefore, the aim of this research is to determine the differences in some morphological characteristics and repetitive strength in relation to the age of handball players. This research includes subjects of three age categories, handball players born in 2009, 2010, and 2011. The sample of measuring instruments consisted of three independent variables - age category of handball players, three variables for the assessment of morphological characteristics (body height, body mass, body mass index) and three variables for the assessment of repetitive strength (sit ups until failure, push-ups until failure and chin ups until failure). All statistical analyzes were implemented within the statistical package IBM SPSS Statistics (Version 20). In all tests of morphological characteristics, significant differences were found (body height, body mass, body mass index) were at the level of p<0.005, while repetitive strength test differences were not found in the push-ups until failure test (p>0.005), but in the sit ups until failure and chin ups until failure tests, significance was determined (p<0.005).